Renal dysfunction and intragraft proMMP9 activity in renal transplant recipients with interstitial fibrosis and tubular atrophy - Racca, María Agustina (2015)
Chronic renal allograft injury is reflected by interstitial fibrosis and tubular atrophy (IF/TA) and by the accumulation of extracellular matrix (ECM). Metalloproteinases (MMPs) are renal physiologic regulators of ECM degradation. Changes in MMPs expression or activity may disturb ECM turnover leading to glomerular scarring and worsening renal function. Our goal was to investigate intragraft MMP2 and MMP9 activities and their correlation with renal dysfunction. Plasma MMP2 and MMP9 activities were analyzed as noninvasive markers of renal allograft deterioration. Transplanted patients were biopsied and histopathologically characterized as IF/TA+ or IF/TA-. Renal function was evaluated by serum creatinine, glomerular filtration rate (GFR) estimated by Modification of Diet in Renal Disease equation and urinary protein/creatinine ratio. Kidney and plasma MMP2 and MMP9 activities were analyzed by zymography. A significant renal dysfunction was observed in IF/TA+ patients. Intragraft proMMP9 showed a significant higher activity in IF/TA+ than in IF/TA- samples and was inversely correlated with the GFR. Intragraft proMMP2 activity tended to increase in IF/TA+ samples, although no statistic significance was reached. Circulating proMMP2 and proMMP9 activities did not show significant differences between groups. Our data provide evidence that correlates intragraft proMMP9 activity with the fibrotic changes and renal dysfunction observed in IF/TA.